Modelo de tutoria baseado na identificação de estilos de aprendizagem dos estudantes: uma proposta para disciplina de probabilidade e estatística na educação a distância - Campos, Rogerio (2019)
Actually, distance education is a reality for many students, whether it is undergraduate, graduate degree or even masters and doctorate degree. The technological mechanisms can also contribute to the process of distance learning and teaching. Therefore, knowing the student and how it learns becomes essential to define what learning style is the most suitable in that process, thus, to develop teaching methodologies that support knowledge experiences. The presented research is based on the theory in the learning styles of Honey and Mumford (2000) and the questionnaire Honey and Alonso (1999). Conceptually speaking, people have preferences on to how to understand the concepts, process it and then build new knowledge. The main objective of this research is to propose a tutoring model that can contribute to the customization of complementary materials and tutoring techniques according to the learning style of distance education students. For that, the methodology of Design Research was applied in a distance administration course in a private college in São Paulo. During the research 86 students of the discipline of Probability and Statistics were interviewed. The research has shown that the customization of complementary materials and activities/assessment related to students' learning style has motivated and improved learning, moreover, it promotes a more interesting and personalized educational experience and consequently more engaging tutoring. Understanding the learning styles in the educational context of distance education allows teachers and tutors to identify prevailing characteristics that can facilitate the elaboration of complementary materials, teaching techniques and also, the final evaluation of a discipline.